Resistance of Recycled Aggregate Concrete (RAC) Subjected to Drying-Wetting Cycles to Attack of Magnesium and Sodium Sulfates - Esam Hewayde; Alireza Pachenari; Hussin Al-Eleaj (Journal of Engineering)
Recycled aggregates were widely used in the concrete industry as a replacement of natural aggregates in the last two decades. In this study, the resistance of concrete mixtures having various levels of recycled aggregate as a replacement of natural coarse aggregate to the attack of magnesium and sodium sulfates was investigated. Five mixtures made with 0%, 25%, 50%, 75%, and 100% recycled aggregate were partially immersed in magnesium and sodium sulfate solutions having concentrations of 2.5%, 4.5%, and 6.5% and subjected to drying-wetting cycles for a total of 10 weeks. Mass losses of concrete specimens owing to the attack of sulfate solutions and the effect of drying-wetting cycles were recorded weekly. Results show that the incorporation of recycled aggregate decreased the compressive strength of concrete at ages of 7 and 28 days. The decline in the compressive strength was more significant when the replacement percentage exceeds 50%. Mass losses of concrete specimens were found to be increased as the level of recycled aggregate increased. Mass losses of concrete specimens having 100% recycled aggregate were approximately as twice as those of concrete specimens having 0% recycled aggregate owing to 10 weeks of partial immersion in magnesium sulfate solutions of concentrations of 2.5%, 4.5%, and 6.5%. The attack of sodium sulfates was less aggressive than that of the magnesium sulfates. Results also show that the reduction in the compressive strength is directly proportional to the mass loss following a linear equation of R-squared value of 0.937.